The Relationship between the Frequency of Attending Islamic Learning Activities and the Development of Students Tolerance Attitudes towards Religious Different - Paramansyah, Arman; Djollong, Andi Fitriani (IJBLE Scientific Publications Community Inc., 2023)
This research explores the link between students' attendance at Islamic learning activities and the development of tolerance towards religious diversity. Conducted in Sukabumi, Indonesia, the study involves 100 high school students from various backgrounds. Results indicate a positive correlation between frequent Islamic studies attendance and heightened tolerance attitudes. The findings emphasize the potential of integrating Islamic learning activities into educational practices to promote inclusivity.